Dynamic changes in the migratory microbial components of colon tissue during different periods of sepsis in an LPS-induced rat model - Hao Xu; Hao Xu; Jia You; Wenqin He; Wenqin He; Lingpeng Pei; Lingpeng Pei; Yue Han; Yue Han; Xueer Wang; Xueer Wang; Zhigang Tian; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Previous studies have shown that bacterial translocation may play an important role in worsening gastrointestinal injury during sepsis. However, the dynamics of specific microbiota components in intestinal tissues at different sepsis stages remain unclear. Rats receiving intraperitoneal lipopolysaccharide (LPS) were sacrificed at 12 h and 48 h post-injection. Routine blood, serum cytokines, and microbiota in colon tissue, colonic contents, and lung tissue at different time points were assessed. Migratory microbial components in colonic tissue at 12 h and 48 h post-LPS were identified using source tracking, characteristic component identification, and abundance difference analyses. Colonic tissue microbiota changed dynamically over time after LPS injection, involving translocation of microbial components from colon contents and lung tissue at different time points. Bacteria migrating to colon tissue at 12 h sepsis were mainly from colonic contents, while those at 48 h were predominantly from the lung tissue. The migratory microbial components in colon tissue were widely associated with blood indicators and colonizing genus abundance and microbiota functionality in colon tissue. In this study, the temporal dynamics of bacterial translocation from various sources into colon tissues at different sepsis progression stages were characterized for the first time, and the species composition of these migrating microbes was delineated. These bacterial migrants may contribute to the pathophysiological processes in sepsis through direct interactions or indirectly by modulating colonic microbiota community structure and function.